2012
DOI: 10.1186/1743-422x-9-101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of microarray data in Arabidopsis transcriptome during compatible interactions with plant viruses

Abstract: BackgroundAt the moment, there are a number of publications describing gene expression profiling in virus-infected plants. Most of the data are limited to specific host-pathogen interactions involving a given virus and a model host plant – usually Arabidopsis thaliana. Even though several summarizing attempts have been made, a general picture of gene expression changes in susceptible virus-host interactions is lacking.MethodsTo analyze transcriptome response to virus infection, we have assembled currently avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 35 publications
2
63
0
1
Order By: Relevance
“…These results also support an existing notion that SA signaling and JA/ET signaling are antagonistic to each other in response to pathogen infection (An and Mou, 2011;Van der Does et al, 2013). In addition, several genes in biological processes, such as carbon metabolism, metabolite transport, cell wall remodeling, protein synthesis and degradation, and photosynthesis, were altered in a manner similar to those described for dicot virus interactions (Whitham et al, 2003(Whitham et al, , 2006Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Hanssen et al, 2011;Postnikova and Nemchinov, 2012). These include genes encoding glutathione S-transferases, cytochrome P450s, glucosyl hydrolases, heat shock proteins, ribosomal components, UPS proteins, and chlorophyll a/ b binding and photosystem-related proteins (Mandadi and Scholthof, 2012).…”
Section: The Panicovirus Complex: New Findings In Plant Virology Usinsupporting
confidence: 86%
See 1 more Smart Citation
“…These results also support an existing notion that SA signaling and JA/ET signaling are antagonistic to each other in response to pathogen infection (An and Mou, 2011;Van der Does et al, 2013). In addition, several genes in biological processes, such as carbon metabolism, metabolite transport, cell wall remodeling, protein synthesis and degradation, and photosynthesis, were altered in a manner similar to those described for dicot virus interactions (Whitham et al, 2003(Whitham et al, , 2006Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Hanssen et al, 2011;Postnikova and Nemchinov, 2012). These include genes encoding glutathione S-transferases, cytochrome P450s, glucosyl hydrolases, heat shock proteins, ribosomal components, UPS proteins, and chlorophyll a/ b binding and photosystem-related proteins (Mandadi and Scholthof, 2012).…”
Section: The Panicovirus Complex: New Findings In Plant Virology Usinsupporting
confidence: 86%
“…Paradoxically, in the molecular genetics era, critical advances in our mechanistic understanding of innate immunity have been made primarily by studying plant pathogenic bacteria and fungi and primarily using dicotyledonous (dicot) hosts. Although there have been studies with viruses such as Tobacco mosaic virus (TMV), Tomato bushy stunt virus (TBSV), Potato virus X (PVX), potyviruses, cucumoviruses, and bromoviruses, almost without exception dicotyledonous plants, primarily Nicotiana benthamiana and Arabidopsis thaliana, were used as experimental hosts (Whitham et al, 2003(Whitham et al, , 2006Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Hanssen et al, 2011;Postnikova and Nemchinov, 2012). Far fewer studies pertain to viruses that infect grasses (the Poaceae).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the tolerant threshold used to define DEGs (P , 0.01) offers more discriminative power between studies. This similarity measure had been employed previously to identify common Arabidopsis transcriptomic responses to different viruses (Postnikova and Nemchinov, 2012). We used the respective dissimilarity (1 -DSC) directly as a distance measure for hierarchical clustering (see "Materials and Methods").…”
Section: Identifying Similar Transcriptional Changes: the Ros Wheelmentioning
confidence: 99%
“…Model plant species, such as Arabidopsis (Arabidopsis thaliana) and Nicotiana benthamiana, have been crucial in determining the mechanics of antiviral defenses. Genome-wide expression studies in these model plants identified networks of genes affected commonly by several plant viruses, whereby diverse DNA and RNA viruses alter genes in primary and secondary metabolism, detoxification, cell wall remodeling, and defense responses (Whitham et al, 2003(Whitham et al, , 2006Ascencio-Ibáñez et al, 2008;García-Marcos et al, 2009;Elena et al, 2011;Hanssen et al, 2011;Postnikova and Nemchinov, 2012). At the cellular level, specific recognition of viral nucleic acids or viral proteins by host resistance gene products inhibits viral replication or accumulation (Kohm et al, 1993;Bendahmane et al, 1999;Ishibashi et al, 2007).…”
mentioning
confidence: 99%